2019
DOI: 10.1016/j.lfs.2019.116580
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin influences endothelin- and serotonin-induced pulmonary artery vasoconstriction in rats

Abstract: Chemerin has been recently identified as a vasoactive adipokine implicated in blood pressure regulation. In this context, we evaluated whether chemerin could influence pulmonary vasoreactive response. Materials and methods: Vascular reactivity to chemerin and to phenylephrine, serotonin and endothelin-1 after chemerin pretreatment was evaluated in rat isolated pulmonary artery versus thoracic aorta with and without endothelium. Vasoreactivity to acetylcholine in presence of nitric oxide (NO)-synthase inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 51 publications
(62 reference statements)
0
13
0
Order By: Relevance
“…Circulating serum levels of chemerin have been reported around 10 −8 mol/L in healthy lean rats and humans (Stejskal et al, 2008;Stelmanska et al, 2013) and increased in pathological conditions, such as diabetes and obesity (Zabel et al, 2005a;Lin et al, 2019). We recently showed that chemerin and its three receptors were expressed in both endothelial cells and SMCs in rat pulmonary arteries (Hanthazi et al, 2019). Here, we showed that primary cultured SMCs from rat pulmonary artery conserved in vitro the expression of chemerin and its three receptors.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Circulating serum levels of chemerin have been reported around 10 −8 mol/L in healthy lean rats and humans (Stejskal et al, 2008;Stelmanska et al, 2013) and increased in pathological conditions, such as diabetes and obesity (Zabel et al, 2005a;Lin et al, 2019). We recently showed that chemerin and its three receptors were expressed in both endothelial cells and SMCs in rat pulmonary arteries (Hanthazi et al, 2019). Here, we showed that primary cultured SMCs from rat pulmonary artery conserved in vitro the expression of chemerin and its three receptors.…”
Section: Discussionmentioning
confidence: 69%
“…RNA concentration was determined using spectrophotometry with a Nanodrop ® ND-1000 (Isogen Life Science, De Meern, Netherlands), and RNA integrity was assessed by visual inspection of GelRed (Biotium, Hayward, CA, United States)-stained agarose gels. Reverse transcription was performed with SuperScript TM II Reverse Transcriptase (Invitrogen by Thermo Fisher Scientific, Merelbeke, Belgium), according to the manufacturer’s instructions ( Hanthazi et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this line, several studies have shown that chemerin is able to promote contractility in blood vessels, including the pulmonary artery, aorta, and superior mesenteric artery in rats and the human saphenous vein [ 146 , 147 , 148 , 149 , 150 ]. It has also been demonstrated that chemerin promotes the increase of blood pressure in rats and mice [ 149 , 151 , 152 , 153 ].…”
Section: Role Of Some Adipokines In Inflammatory Processes Associamentioning
confidence: 99%